Um modelo de medição para processos de desenvolvimento de software - Eduardo Pereira Borges (2003)
In software development, different kinds of measures provide important information about ongoing projects and the quality of products. Moreover, quantitative measures are a way of precisely registering the memory of the projects of an organization, forming a historical baselinewhich can be used to characterize, adapt and progressively improve the processes being used. This work exploits common aspects of development processes widely used by the software industry and proposes a generic measuring framework, which can be applied to most of them. Popular techniques are utilized to select and define a set of measures in order to quantitatively characterize some key aspects of the development cycle (cost, size of products, number of defects, progress, schedule and requirements stability) and provide data that contribute to improve the quality of products, productivity and predictability of processes.